Konsep Pengembangan Kecerdasan Buatan sebagai Representasi Arsitek: Kajian Literatur - Johan Agung Pramono Hambadjawa; Khaerunnisa (Universitas Muhammadiyah Palembang, 2024)
Human Architects cannot be replaced, even with Artificial Intelligence, but Artificial Intelligence could represent an Architect, especially in problem-solving. An architect is not eternal. Brilliant ideas vanished alongside the physical form of an Architect. By respecting the Architect who had left this world while simultaneously keeping the brilliant ideas alive, Artificial Intelligence could represent the Architect as a legacy that always lives through unique problem-solving solutions according to each individual. Using the methods done in the past, such as GANs, writers design the shape of an Artificial Intelligence by using data collection methods such as manual input, then realizing the Artificial Intelligence through machine learning, and later will be available through a digital application like a book. This book could interact with its reader. This research uses descriptive qualitative methods based on a literature review on Artificial Intelligence (AI) and the world of architecture. The results obtained are that humans will live side by side with technology, and in the future.